2022
DOI: 10.1080/13510002.2022.2096339
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane reduces lipopolysaccharide-induced apoptosis and pulmonary fibrosis in the RAW264.7 cells and mice models to ameliorate acute lung injury by eliminating oxidative damages

Abstract: Objectives Sevoflurane is identified as an effective candidate drug for acute lung injury (ALI) treatment, but its curing effects and detailed mechanisms have not been fully disclosed. The present study was designed to resolve this academic issue. Methods The ALI mice models were established, and Hematoxylin-eosin staining assay was performed to examine tissue morphologies. Cell viability was determined by CCK-8 assay, and Annexin V-FITC/PI double staining assay was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…As previously reported, the classical Keap1-Nrf2 pathway is pivotal for regulating oxidative stress, and in oxidative stress conditions, the activated Nrf2 transfers from the cytoplasm to the nucleus to activate the downstream anti-oxidant effectors through binding to ARE [14]. Through LPS promotion and NAC suppression, we found that the related genes on the pathway of Keap1-Nrf2 had changed accordingly.…”
Section: Signi Cantly Increased Ros Release From Neutrophils In the L...supporting
confidence: 66%
See 1 more Smart Citation
“…As previously reported, the classical Keap1-Nrf2 pathway is pivotal for regulating oxidative stress, and in oxidative stress conditions, the activated Nrf2 transfers from the cytoplasm to the nucleus to activate the downstream anti-oxidant effectors through binding to ARE [14]. Through LPS promotion and NAC suppression, we found that the related genes on the pathway of Keap1-Nrf2 had changed accordingly.…”
Section: Signi Cantly Increased Ros Release From Neutrophils In the L...supporting
confidence: 66%
“…Many studies have suggested that regulation of Keap1-Nrf2 signaling pathways can affect the development of lung injury [14]. Speci cally, Huang et al [15] suggest that this pathway regulates endoplasmic reticulum stress, apoptosis, and autophagy to attenuate LPS-induced ALI.…”
Section: Introductionmentioning
confidence: 99%
“…Data shown are the mean ± SD (n = 3 per group). Data were compared by unpaired ttest or two-way ANOVA using a significance level of p < 0.05. ischemia, 27,28 we found that it was KLF5 that linked the regulatory effects of Sevo on macrophage infiltration to ITGB2 expression. In conclusion, Sevo attenuated I/R-associated liver damage in mice by exerting its anti-apoptotic and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 80%
“…Propidium Iodide (PI) is a nucleic acid dye that causes the cell nucleus to become red by damaging cell membranes. Thus, Annexin V with PI can be used to distinguish cells at different stages of apoptosis [ 55 ]. MRC-5 cells at logarithmic growth phase were seeded in 6-well plates (1 × 10 5 ).…”
Section: Methodsmentioning
confidence: 99%